Applied technologies to prolong drug release: an integrative review - Ana Vithória da Silva Melo; Danilo Augusto Ferreira Fontes (Universidade Estadual de Alagoas, 2023)
Extended-release systems have several advantages, such as greater availability of the drug in the bloodstream and fewer side effects, being properly applied to drugs that have a short biological half-life, requiring a "medium" for the drug to remain for a period of time. extended, reaching its destination. The objective of this study was to show three technologies currently used in order to prolong the release/action of the drug. An integrative review was carried out, collecting articles from the following databases: VHL, Google academic, Scielo and Pubmed, published in the last 10 years. Thus, the importance of these systems and their applicability was demonstrated, including the benefits for the patient, when using a drug with an extended effect, since it is usually necessary to ingest several doses, so that the therapeutic effect is obtained. It is concluded that the implementation of these systems has satisfactory performance against drugs that do not use these technologies, favoring the patient with a better therapeutic effect, due to easier adherence.